2015
DOI: 10.1177/1059601115577514
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing, Abusive Supervision, and Support

Abstract: Knowledge sharing is essential for achieving sustainable competitive advantages for organizations. Yet, there is a paucity of studies examining how a supervisor's behavior, particularly, abusive supervision may become a barrier of individuals' knowledge sharing. Drawing on insights from social exchange theory, this study investigates the influence of abusive supervision on knowledge sharing, moderated by support from organization and coworker. Consistent with our hypotheses, abused employees do not share their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 67 publications
2
80
0
1
Order By: Relevance
“…In line with previous studies (e.g., Burke et al, ; Holste & Fields, ), this one demonstrated trust as an essential factor in promoting knowledge sharing. Considering the importance of knowledge sharing (Kim et al, ), the results are meaningful as they highlight the critical role of trust in leaders and coworkers in the knowledge‐sharing process. Furthermore, the results clarified the importance of the interactions between trust and task performance in shaping the level of knowledge sharing.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In line with previous studies (e.g., Burke et al, ; Holste & Fields, ), this one demonstrated trust as an essential factor in promoting knowledge sharing. Considering the importance of knowledge sharing (Kim et al, ), the results are meaningful as they highlight the critical role of trust in leaders and coworkers in the knowledge‐sharing process. Furthermore, the results clarified the importance of the interactions between trust and task performance in shaping the level of knowledge sharing.…”
Section: Discussionmentioning
confidence: 82%
“…Considering that the core component of trust is risk taking, employees may consider it a risk that their leaders might not fairly evaluate their contribution, which may lead to high turnover intention when trust in the leader is low (Dirks & Ferrin, ; Mayer et al, ). Moreover, sharing knowledge can be perceived as a risky behavior, because knowledge providers may lose their competitive advantages by sharing their knowledge (Kim, Kim, & Yun, ; Wang & Noe, ). Previous research has highlighted trust as an essential factor in the knowledge‐sharing process (Burke et al, ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…We used the seven‐item scale that Srivastava et al () produced by combining Faraj and Sproull's () four‐item knowledge sharing scale and Durham ()'s three‐item information sharing scale. Srivastava et al () have validated the combined seven‐item scale, and subsequent research (e.g., Kim, Kim, & Yun, ; Kim & Yun, ) has used the Srivastava et al () seven‐item scale to measure knowledge sharing. The items were “This employee shares his/her special knowledge and expertise with other employees,” “If this employee has some special knowledge about how to perform the task, he/she is likely to tell others about it,” “This employee exchanges information, knowledge, and sharing of skills with other employees,” “This employee freely provides others with hard‐to‐find knowledge or specialized skills,” “This employee helps others in developing relevant strategies,” “This employee shares a lot of information with other employees,” and “This employee offers lots of suggestions to other employees.” A confirmatory factor analysis (CFA) of the seven items from the two scales indicated an acceptable level of fit for a one‐factor model ( χ 2 (12) = 31.47, p < .01; GFI = .95, CFI = .99, RMSEA = .10).…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with what has been discovered for other detrimental stressors, as reviewed above, it is little surprising that abusive supervision increases emotional exhaustion and decreases job performance at the individual level, although individuals' cognitive reappraisal (Chi & Liang, ), conscientiousness (Nandkeolyar et al, ), and psychological capital (Li et al, ) ameliorate such detrimental effects. At the team level, team member support (Hobman, Restubog, Bordia, & Tang, ) and organizational support (Kim, Kim, & Yun, ) have been shown to attenuate the undesirable effects of abusive supervision. Therefore, expanding the concept of stressors to the team level is informative for studies on destructive leadership (such as abusive supervision) once such leadership behaviors are understood and theorized as stressors.…”
Section: Future Research Agendamentioning
confidence: 99%